Of Lunatics, Lovers, and Poets: The Conversation about Poetry in Shakespeare's A Midsummer Night's Dream. Issue 2 (November 2018) - Carlson, Donald
Abstract : Individual works of poetry and drama often contribute to a conversation that spans centuries, but A Midsummer Night's Dream contains a very specific dialogue in which Shakespeare takes the Jesuit priest-poet Robert Southwell for an interlocutor. Shakespeare creates this conversation by echoing Southwell's published work. By the first staging of A Midsummer Night's Dream, around 1595 or 1596, Southwell had endured a martyr's death; but that didn't stop Shakespeare from responding to the prescriptions laid down by Southwell about the proper way for Christian poets to write. His prefatory letter and introductory poem to the posthumous volume St. Peters Complaint make clear that Christian poets whose poems are not overtly devotional are squandering their talent. He remonstrates with such poets – one in particular, whom Southwell addresses as his "belov'd cousen" – to chasten themselves and to write poetry more in the vein of the reverent and improving verses included in Southwell's own volume. Through the character of Theseus, especially, and in the structure of the play, more generally, Shakespeare replies to Southwell. Shakespeare doesn't simply reject Southwell, but rather evokes an understanding of piety and poetry consistent with the pre-Reformation, late medieval Church. This understanding is one that allows room for juxtaposing the sacred and the profane as opposed to championing one at the expense of the other.